Perioperative Doppler measurements of renal perfusion are associated with acute kidney injury in patients undergoing cardiac surgery - Johan Lyngklip Hermansen (Nature Portfolio, 2021)
Abstract Acute kidney injury (AKI) is a frequent and severe complication in cardiac surgery. Normal renal function is dependent on adequate renal perfusion, which may be altered in the perioperative period. Renal perfusion can be assessed with Doppler measurement. We aimed to determine the association between Doppler measurements of renal perfusion and the development of AKI. This was a prospective, observational study of 100 patients with ≥ one risk factor for postoperative AKI undergoing open-heart surgery. Doppler ultrasound examinations were performed before surgery and on the first and fourth postoperative day. AKI was defined according to the KDIGO criteria and subdivided into mild (KDIGO stage 1) and severe AKI (KDIGO stage 2 + 3). Thirty-three patients developed AKI, 25 developed mild and eight developed severe AKI. Abnormal renal venous flow pattern on the first postoperative day was significantly associated with the development of severe AKI (OR 8.54 (95% CI 1.01; 72.2), P = 0.046), as were portal pulsatility fraction (OR 1.07 (95% CI 1.02; 1.13), P = 0.005). Point-of-care Doppler ultrasound measurements of renal perfusion are associated with the development of AKI after cardiac surgery. Renal and portal Doppler ultrasonography can be used to identify patients at high risk or very low risk of AKI after cardiac surgery.